Translator plagiarism and eclectic translations - Michael Studemund-Halévy (Cuadernos AISPI)
Literature lives on translation, is fed by  translation. Judezmo literature may be absent from world literature, but world literature is omnipresent in Judezmo literature. Judezmo literature is a literature of translation (adaptation, imitation, rewriting, plagiarism), that is, a literature of adaptation of European works in terms of inspiration, influence or models of imitation. Reliance on foreign-language sources became a characteristic of Sephardic fiction that tended to receive influences rather than exert them.